A Wind Energy Harvester Based on Piezoelectric Magnetic Compound. Issue 19 (29th July 2022) - He, Lipeng; Gu, Xiangfeng; Wang, Shuangjian; Liu, Xuejin; Hu, Renhui; Cheng, Guangming
Abstract : Herein, an energy harvester relying on the combination of piezoelectric and electromagnetic power generation is developed to increase the power generation and realize the force deformation of the piezoelectric sheets through the interaction between the exciting and mass magnets, thus avoiding mechanical collision and abrasion and improving the operational life span. The theoretical analysis for the magnetic movement, winding moment, and resilience strain is done, and the maximum shift of the rectangular and circular piezoelectric sheets is obtained through simulation. Experimentally, the device achieves the highest output voltage of 28.4 V when there are two exciting magnets and in mutual repulsion with the mass magnet. For an external resistance of 2 kΩ, the device outputs a maximum power of 20.48 mW. The device can convert wind energy from the environment into electricity and power other devices via circuit storage. Abstract : This article presents an energy harvester that achieves piezoelectric and electromagnetic power generation through the action of excitation and mass magnets. The device is designed to avoid mechanical collisions and improve the working life. And the electricity generated can be stored for other equipment.